EP483 Biomarker prediction of outcome varies by race in uterine serous carcinoma. (1st November 2019) - Bussies, P; George, S; Pinto, A; Huang, M; Slomovitz, B; Schlumbrecht, M
Abstract : Introduction/Background: Minority women are known to have higher risk for uterine serous carcinoma (USC). Limited data exist to establish reliability of prognostic biomarkers by race in these patients. Our objective was to evaluate patterns of clinical and pathologic biomarkers and their effects on outcome between white and non-white patients. Methodology: A retrospective review was completed on all women diagnosed with USC between 2005 and 2017. Hematologic parameters and CA125 were ascertained at time of diagnosis, and pathology reports assessed for tumor size, lymphovascular space invasion (LVSI), and immunohistochemical (IHC) staining (>1% tumor cells) for estrogen receptor (ER) and progesterone receptor (PR). Statistics were done using chi-square, Cox proportional hazards, and the Kaplan-Meier method, with significance set at p<0.05. Results: 59 patients were non-white (35.5%), 57 of whom were black; 107 were white (64.5%). At diagnosis, no differences were seen in mean CA125 levels (745 white vs. 630 non-white, p=0.83) or mean platelet levels (320K white vs. 354K non-white). There were no differences in proportion of women with LVSI or positive staining for ER or PR by race (all p>0.05). Primary tumors were larger in non-white patients, though this was not significant (55 mm vs 43 mm, p=0.06). Thrombocytosis (platelets ≥450K) was associated with worse overall survival (OS) in whites (HR 4.38 [CI 1.55–12.34], p=0.005) but not in non-whites (HR 2.05 [CI 0.73–5.74], p=0.17). For both races, tumor size and higher stage were negatively associated with OS (p<0.05), while ER and PR had no effect. Median OS was worse for non-whites without thrombocytosis (30.1 vs 38.4 months), but was better for non-whites when thrombocytosis was present (22.1 vs 16.4 months) (p=0.01) (figure 1). Conclusion: Biomarker variation is minimal by race in USC, while the effect of thrombocytosis on OS varies significantly by race. Further investigation is warranted to elucidate the mechanism behind this observation. Disclosure: Nothing to disclose.